Superfast Water Transport Zwitterionic Polymeric Nanofluidic Membrane Reinforced by Metal–Organic Frameworks. Issue 38 (4th August 2021) - Ji, Yan‐Li; Gu, Bing‐Xin; Xie, Shi‐Jie; Yin, Ming‐Jie; Qian, Wei‐Jie; Zhao, Qiang; Hung, Wei‐Song; Lee, Kueir‐Rarn; Zhou, Yong; An, Quan‐Fu; Gao, Cong‐Jie
Abstract: Nanofluidics derived from low‐dimensional nanosheets and protein nanochannels are crucial for advanced catalysis, sensing, and separation. However, polymer nanofluidics is halted by complicated preparation and miniaturized sizes. This work reports the bottom‐up synthesis of modular nanofluidics by confined growth of ultrathin metal–organic frameworks (MOFs) in a polymer membrane consisting of zwitterionic dopamine nanoparticles (ZNPs). The confined growth of the MOFs on the ZNPs reduces the chain entanglement between the ZNPs, leading to stiff interfacial channels enhancing the nanofluidic transport of water molecules through the membrane. As such, the water permeability and solute selectivity of MOF@ZNPM are one magnitude improved, leading to a record‐high performance among all polymer nanofiltration membranes. Both the experimental work and the molecular dynamics simulations confirm that the water transport is shifted from high‐friction‐resistance conventional viscous flow to ultrafast nanofluidic flow as a result of rigid and continuous nanochannels in MOF@ZNPM. Abstract : A rigid‐scaffold‐reinforced polymeric nanoparticles' interfacial channel strategy is proposed for fabricating nanofluidic membranes that exhibit water permeance and dye/salt selectivity that are 1–2 orders of magnitude higher than conventional polymeric membranes. The unprecedented separation performance is due to the paradigm shift of water transport from conventional viscous flow to ultrafast nanofluidic flow in the membrane nanofluidics.